ANALYSIS OF FACTORS AFFECTING PATIENT SATISFACTION IN JKN SYSTEM: PATIENT CHARACTERISTICS, JKN SERVICES, AND PHARMACY SERVICES - Satibi Satibi (Indonesian Journal of Pharmacy, 2015)
National Health Insurance (JKN) is a health insurance system by using mechanisms of social health insurance held by BPJS. Satisfaction of participants will affect the sustainability of the system JKN. Factors affecting patient satisfaction are patient characteristics, JKN services, and pharmacy services. This study aimed to examine the influence of patient characteristics, JKN services, and pharmacy services with patient satisfaction in the primary health facilities. This research is analytic with cross sectional survey design. Data taken quantitatively by using questionnaires and equipped with qualitative data from interviews to deepen the findings in the field. The sampling technique used is random sampling for primary health facilities with a total sample of 55 health facilities and purposive sampling for a sample of patients with a total sample of 300 respondents. Data were analyzed using Chi-Square to examine relationship between patient characteristics with patient satisfaction and linear regression to examine the relationship between services in JKN system with patient satisfaction. Characteristics of patients who have a significant relationship to the patient satisfaction is education (p=0.020), employment (p = 0.001), income (p = 0.000), and membership status (p = 0.005).There is a significant relationship between services in JKN system includes JKN sevices with patient satisfaction (p = 0.000) and pharmacy service in the era of JKN with patient satisfaction (p = 0.000). The conclusion of this study is the patient characteristics include education, employment, income and membership status, and service in JKN system includes JKN services and pharmacy services in the era of JKN has a significant relationship with the satisfaction of patients at primary health facilities.Keywords: patient characteristics, JKN services, pharmacy services, patient satisfaction